2008
DOI: 10.1152/ajplung.00421.2007
|View full text |Cite
|
Sign up to set email alerts
|

Airway smooth muscle cell tone amplifies contractile function in the presence of chronic cyclic strain

Abstract: Chronic contractile activation, or tone, in asthma coupled with continuous stretching due to breathing may be involved in altering the contractile function of airway smooth muscle (ASM). Previously, we (11) showed that cytoskeletal remodeling and stiffening responses to acute (2 h) localized stresses were modulated by the level of contractile activation of ASM. Here, we investigated if altered contractility in response to chronic mechanical strain was dependent on repeated modulation of contractile tone. Cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Of note, the effects of methacholine were similar to those of TGF-b, and shown to be mediated via enhanced release of TGF-b [42]. In vitro, it has been shown that muscarinic receptor stimulation, in combination with mechanical strain, can induce a-sm-actin and sm-myosin mRNA expression in bovine tracheal smooth muscle strips, and myosin light-chain kinase expression in human airway smooth muscle cells [43,44]. Moreover, contraction of airway smooth muscle cells induces TGF-b activation [45].…”
Section: Bronchoconstriction As a Driver Of Airway Remodelingmentioning
confidence: 85%
“…Of note, the effects of methacholine were similar to those of TGF-b, and shown to be mediated via enhanced release of TGF-b [42]. In vitro, it has been shown that muscarinic receptor stimulation, in combination with mechanical strain, can induce a-sm-actin and sm-myosin mRNA expression in bovine tracheal smooth muscle strips, and myosin light-chain kinase expression in human airway smooth muscle cells [43,44]. Moreover, contraction of airway smooth muscle cells induces TGF-b activation [45].…”
Section: Bronchoconstriction As a Driver Of Airway Remodelingmentioning
confidence: 85%
“…Although not possible with the current iteration of microfabricated tissue gauges, it may also be important to determine whether applying dynamic mechanical strain alters the contractility of ASM in 3D microtissues. In traditional 2D cultures of ASM, dynamic mechanical strain can have potent effects, acutely eliciting cytoskeletal fluidization (40) and depending on the exact nature of the strain regime it can elicit chronic changes in ASM phenotype and function (22,44), but it is currently unclear whether 3D cell geometry may alter these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of live and fixed microtissues was performed on a Leica DM IRB microscope with a ϫ10 or ϫ20 lens, and images were captured with a PCO Sensicam CCD camera with custom software [Beadtracker (22)]. Images were uniformly adjusted for brightness and contrast only, ensuring that no details were obscured.…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways are also involved in the acquisition of contractile protein expression by TGF-β via transcriptional and translational processes Goldsmith et al, 2006;Zhou et al, 2005) and can be activated by muscarinic receptor stimulation (Halayko et al, 2008). Indeed, the expression of myosin light-chain kinase was augmented by carbachol in human airway smooth muscle cells exposed to cyclical mechanical strain (Fairbank et al, 2008). Additionally, we recently described that muscarinic receptor stimulation enhanced the TGF-β1-induced contractile protein expression in human airway smooth muscle cells (Oenema et al, 2010b).…”
Section: Mesenchymal Cellsmentioning
confidence: 98%